PENGARUH LATIHAN RENTANG PERGERAKAN SENDI TERHADAP KEKUATAN OTOT, LUAS GERAK SENDI DAN KEMAMPUAN FUNGSIONAL PASIEN STROKE DI RS HUSADA JAKARTA - ojs, admin; Suarti, Ni Made; Rohani, Rohani (Sekolah Tinggi Ilmu Kesehatan RS Husada, 2017)
Stroke is a clinical syndrome caused by blood supply disruption to the brain, it has an effect on many functions of the body. The most obvious motoric deficit effect is hemiparese. The aim of this study is to identify the effect of RPS exercise to muscle strength, joint range of motion and functional ability of patient with stroke at Sint Carolus Hospital Jakarta. A quasi experimental with control group pretest-posttest design was used in this study. The total samples of 30 patients with stroke were selected by a consecutive sampling method. The result showed that muscle strength (p=0,000) and functional ability (p=0,000) were significantly improved after given RPS exercise. This study recommended on the needs of further research, and the use of this exercise as an independent nursing intervention in providing care to stroke patient.